V. Models of Dissent: The Chicano Movement in the Roman Catholic Church. Issue 1 (23rd May 2018) - Steidl, Jason
Abstract : This contribution to the roundtable will compare two forms of protest in the church—one that is radical and challenges the church from the outside, and the other that is institutional and challenges the church from the inside. For case studies, I will compare Católicos Por La Raza (CPLR), a group of Chicano students that employed dramatic demonstrations in its protest of the Catholic Church, and PADRES, an organization of Catholic priests that utilized the tools at its disposal to challenge racism from within the hierarchy. I will outline the ecclesiologies of CPLR and PADRES, the ways in which these visions led to differing means of dissent, and the successes and failures of each group.